2021
DOI: 10.24252/elstic-ij.v1i2.21967
|View full text |Cite
|
Sign up to set email alerts
|

Elt Material for Biology Education Department Students: What Are the Students' Needs?

Abstract: This research is aimed to analyze the need of Biology Education Department Students at UIN Alauddin Makassar. Based on the preliminary study, the researcher found that English subject on Biology Education does not have a specific syllabus and also the material is not through the need analysis based on priorities needed by students of Biology Education Department. The research design used in this study was survey method. This need analysis comprises of Target Situation Analysis, Present Situation Analysis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…In the present study, students showed less interest in improving reading skills. This finding is in contrast to previous findings in Makassar [2]. Videos in biological topics may help students with low reading habits to improve their English proficiencies.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the present study, students showed less interest in improving reading skills. This finding is in contrast to previous findings in Makassar [2]. Videos in biological topics may help students with low reading habits to improve their English proficiencies.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study aimed to describe students' needs and expectations in learning English for Biology. This study then further explored and elaborated the findings from previous studies [2,3]. This study has a very important contribution to ensure that the English language teaching material delivered (in the students' handbook) compromises with the needs of students.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations